Pendampingan santri Pondok Pesantren Nurul Qomar dalam pencegahan dan penatalaksanaan penyakit akibat parasit - Azhari, Dalilah; Anwar, Chairil; Prasasty, Gita Dwi; Handayani, Dwi; Santoso, Budi; Purnomo, Abdul Harits; Shiddiq, Abdul Halim; Nahrani, Ulya; Izzulhaq, Muhammad Agung; Martadiansyah, Abarham (Jurnal Pengabdian Masyarakat: Humanity and Medicine, 2023)
Assistance for Nurul Qomar Islamic Boarding School Student in Prevention and Management of Diseases Due to Parasites. Indonesia, which has a tropical climate, causes problems in terms of health, namely the existence of tropical infectious parasitic diseases such as pediculosis capitis and scabies. Pediculosis capitis and scabiasis often occur in high residential densities, including Islamic boarding schools. Community service activities are carried out by diagnosing, treating and educating pediculosis capitis and scabies regarding disease definitions, disease symptoms, transmission, and disease prevention. Disease education and outreach events were held in the hall of the Nurul Qomar Islamic Boarding School using LCD projectors and posters as media. A total of 161 people who were present during the education consisted of 154 students, consisting of 58 male students and 96 female students, 2 ustadz and 5 ustadzah who are also teaching teachers at Islamic boarding schools. As many as 40 people (15 female students and 25 male students) clinically suffered from scabies. Meanwhile, in the examination of head lice from 154 students, 30 students were found to be infested with pediculosis capitis. Treatment was carried out for every student with positive indications of scabies and pediculosis, as well as students who had other skin diseases due to bacterial and fungal infections.